Environmental Contamination and Antimicrobial Resistance Patterns in Hemodialysis Units at Tripoli University Hospital - Mustafa Alkawash; Aya Muktar; Asma Elkammoshi; Hamza Abouda; Khuloud Soukni (Khalij-Libya Journal of Dental and Medical Research, 2025)
Continuing care Patients receiving hemodialysis for end-stage renal failure have increased risks of bloodstream-associated infections because of their weakened immune systems and the use of catheters to control their blood flow. Staphylococcus species are a common cause of hemodialysis catheter-related bloodstream infections. This study aimed to identify the source of bacterial contamination of dialysis wards and contamination of hemodialysis equipment and their antimicrobial resistance patterns. Swabs were used for collecting all of the samples, which were then sent to the lab for microbiological testing. In this data, the hemodialysis device has fewer microorganisms than the surrounding environment of the patient. However, the majority of Staphylococcus species were detected on the hemodialysis beds (n=9), particularly on regions that healthcare staff often touched. The most common type of Staphylococcus species found was coagulase-negative Staphylococcus. Even more unexpectedly, methicillin resistance (MRSA) was found in the of Staphylococcus species، followed by Bacillus spp, which were located in the dialysis area and staff room, where Bacillus subtilis (21%), Bacillus cereus (16%), while the least were Bacillus pumilus (6%) and Bacillus licheniformis (5%) , additionally present Gram negative rods were Klebsiella pneumonia (60%) and Escherichia coli (40%). This result implies that the related microorganisms in hemodialysis devices are substantially polluted. This study can be used to evaluate the risk of infection by contamination and to create a cleaning method that will help hemodialysis patients stay away from bloodstream infections.